A likelihood-ratio framework for evaluating results of forensic gunshot-residue analysis. (July 2022) - Osnat, Israelsohn Azulay; Hila, Rosengarten; Amit, Cohen; Yigal, Zidon; Zohar, Pasternak
Abstract: When reporting results of Gunshot Residue (GSR) analysis from a person suspected to be involved in a recent shooting, most forensic experts only provide the court with the raw results (i.e. the number of GSR particles found) and a disclaimer that a positive finding does not prove that the suspect was involved in a firearm shooting incident whilst a negative finding does not prove that he was not. Probabilistic analysis of the GSR results provides more value to the court, so the present study calculated likelihood ratio (LR) values for finding 0–8 characteristic GSR particles (containing Lead, Barium and Antimony) on a suspect's hands, based on the available GSR data from the published literature as well as studies by the authors. Defense propositions, i.e. modes for GSR acquisition other than involvement in a shooting event, were divided into three broad categories: low, medium and heavy background. For each background level and number of GSR particles found, minimal and maximal LR values were calculated. Thus, for each proposition the defense provides for the presence of GSR on the defendant's hands, the forensic expert can provide a possible set of minimal and maximal LR values, leaving the court to examine the defendant's contention and decide which of the three background modes is more plausible according to the circumstances of the specific case. Highlights: We calculate likelihood ratio values for finding characteristic GSR particles on a suspect. Defense propositions are divided into three broad categories: low, medium and heavy background. LR calculations are based on the available GSR data from published literature and studies.